Educação, devoção e romanização : a história dos salesianos em Sergipe e a devoção a Nossa Senhora Auxiliadora (1902- 1958) - Andrade, Edla Tuane Monteiro (2018)
In 1890, in Brazil, the powers of the State and Church are separated. The Romanization process made official a change of attitude of Catholicism in the face of the problems that had arisen during the Old Republic, in which it sought to broaden its pretensions of influence over society. Among the ambitions to be achieved are: the importation of European Religious Orders and Congregations (Salesians), the installation of a new devotional configuration in the mold of Roman Catholicism; the propagation of a network of private education institutions to form elites. In Sergipe, we analyze the unfolding of the process of Romanization before the establishment and development of the Salesian Congregation, through educational practices and the diffusion of the Devotion to Our Lady Help of Christians. In the Brazilian territory, devotion to Our Lady Help of Christians is widespread and devoted in its basic regions, cities and states. Based in the field of Cultural History, with an emphasis on History and Religion, this research aims to make an analytical study from the History and Salesian Memory, between 1902 and 1958, including the private and family devotional system, and how it was established in the social and history of sergipanos. Understanding this way, the role of Salesian Education, strategic form of diffusion of the process of romanization. The research deals with the concepts of religious experience as an object in the field of history (CERTAU, 1996), representation (CHARTIER, 1990) and symbolic power / religious field (BOURDIEU, 2004). Methodologically, the work consists of the analysis of sources on the presence of the Catholic Church in Sergipe in diverse institutions and places of memory.